Development of digital technologies in Russia: regional aspects - Arkhipova, Marina Yuryevna; Sirotin, Vyacheslav Pavlovich (Economy of Regions, 2019)
The modern economy is on the way to a new technological order based on knowledge-intensive industries relying on digital technologies. This transition’s possible effects are yet to be sufficiently studied as they require thorough analysis and the use of the appropriate tools. Moreover, it is necessary to develop new indicators considering the specificity of the economy’s digitalization. The article presents a methodology for studying the phenomena of the digital economy and digital divide in Russian regions. Using the methodology, we developed new indicators, approaches and techniques for studying the changes at different levels of hierarchy and the effects of their impact. In the first block we established a composite indicator for studying regional imbalances in the development of digital economy. This indicator has several advantages as it takes into account the availability of the basic information and communication technologies and wired network services. In the second block we introduced the method of classifying the Russian regions by the level of digital technologies development. Differences in the mean values of variables across clusters allow determining the magnitude of the inequality in the technology’s dissemination between the groups of regions. In the third block we identified the key determinants of digital development and information inequality based on the panel data regression models. We built separate models for the information and communication technology accessibility index and its two sub-indices, assuming they were influenced by different and divergent factors. Defining the effective institutional mechanisms for digital development will determine the direction for boosting the competitiveness of the Russian regions and engage additional sources of economic growth. Furthermore, it will help increasing innovation activity and reducing the digital divide.